Representasi Nilai – Nilai Karakter Masyarakat Minangkabau pada Film Surau dan Silek - Ayu Khairunnisa; Effiati Juliana Hasibuan; Novri Novri (Universitas Medan Area, 2021)
The title of this research is the Representation of the Value of Minangkabau Characters in the Film Surau and Silek. This research is motivated by the unique principles of life of the Minangkabau people which make Islam the basis of Adat and Culture. The Minangkabau tribe has a traditional principle of